A psycho-emotional framework for environmental education: integrating ecopsychology, eco-emotions, and eco-narratives - Nair K. J., Harish; Chithra, Gandhapodi K. (Frontiers in Education, 2025)
In response to the escalating ecological crises, this study aims to propose a narrative-enhanced, psycho-emotional framework in environment education. This research integrates three interdisciplinary domains, ecopsychology, eco-emotions, and environmental narratives, to construct a method that strengthens learners’ ecological identity, emotional resilience, and pro-environmental behavior. Drawing from theories of environmental psychology, emotional regulation, and narrative pedagogy, the study explores how affective connections with nature, such as biophilia, topophilia, and eco-hope, can be cultivated through narrative-enhanced education. Using a qualitative approach, the paper analyses the influence of eco-emotions (both negative and positive) on learners’ attitudes and behaviors toward climate action, highlighting their potential for eco-consciousness. The findings emphasize that narrative-enhanced environmental education (NEEE) promotes psychological well-being, fosters human-nature attachment, and prepares learners to engage with climate actions with empathy. The study advocates for a paradigm shift in environmental education toward a method rooted in eco-emotions, ecological identity, and symbiotic learning. The paper advocates a paradigm shift in environmental education toward an emotionally rooted, identity-driven, and symbiotic model that promotes long-term ecological stewardship and a symbiocentric future.